2018
DOI: 10.1097/brs.0000000000002669
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Attenuates Multifidus Muscles Injury and Atrophy After Posterior Lumbar Spine Surgery by Suppressing Inflammation and Oxidative Stress in a Rat Model

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It has been reported that VC plays a positive role in stimulating skeletal muscle growth and intake of VC could ameliorate muscle atrophy, mainly through antioxidant and antiinflammatory effects. 26,41,42 We first investigated whether the effect of VC on pMuSC was related to its antioxidant or collagen synthesis activity, but the results indicated that the proliferation and myogenic properties of pMuSCs could not be simply attributed to ROS scavengers and collagen promotion. Subsequently, we proved that VC could stimulate the PI3K/ AKT/mTOR signaling in pMuSCs, providing new insights into the research on the mechanism of VC on skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that VC plays a positive role in stimulating skeletal muscle growth and intake of VC could ameliorate muscle atrophy, mainly through antioxidant and antiinflammatory effects. 26,41,42 We first investigated whether the effect of VC on pMuSC was related to its antioxidant or collagen synthesis activity, but the results indicated that the proliferation and myogenic properties of pMuSCs could not be simply attributed to ROS scavengers and collagen promotion. Subsequently, we proved that VC could stimulate the PI3K/ AKT/mTOR signaling in pMuSCs, providing new insights into the research on the mechanism of VC on skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Recent studies also demonstrate that VC is associated with epigenetic reprogramming [22][23][24] and muscle regeneration. [25][26][27] Besides, VC has been widely used in the ex vivo culture of various cell types such as cardiac progenitor cells, 28 osteoblasts, 29 and induced pluripotent stem cells. 30 However, the effect of VC on the ex vivo proliferation and differentiation of MuSCs has not been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Fruits, vegetables, and their extracts are the best sources of ascorbic acid [3]. Despite the beneficial effects of these antioxidants against inflammation, oxidative stress, and chronic gastrointestinal disorders via quenching of oxidizing free radicals [4,5,6,7,8], their practical applications are challenging due to their rapid degradation and sensitivity to environmental factors, e.g., oxygen, heat, and light. Nanoencapsulation has been proposed as an efficient strategy to overcome these obstacles [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al assessed the inflammation, steatosis, and fibrosis of muscle by quantitative real-time polymerase chain reaction, histological, and immunohistochemical analysis. It was found that the marker genes and scores of fibrosis and steatosis in the ascorbic acid group were significantly lower than those in the control group at 14 and 28 days after [63]. Severe muscle degeneration, inflammation, and decreased blood vessels are commonly observed in biopsies of people with lumbar lesions compared to normative data.…”
Section: Oxidative Stress and Inflammation Of Multifidusmentioning
confidence: 91%